The Quest for Restoration of the African Renaissance through Indigenous African Music and Globalisation: A Case Study of South Africa - Sakhiseni Joseph Yende; Nsizwazonke Ephraim Yende (E-Journal of Humanities, Arts and Social Sciences)
Rooted in the philosophy of Ubuntu, this article contends that the revival of indigenous South African music transcends mere cultural revitalisation; it emerges as a transformative force for community empowerment. Through the cultivation of creativity, the bridging of generational divides, and the nurturing of a profound sense of belonging, Ubuntu reaffirms the intrinsic worth of everyone’s contribution to the collective cultural legacy. The African Renaissance, a dynamic movement dedicated to rejuvenating Africa’s cultural, political, and economic identity, finds its heartbeat in the resurgence of indigenous African music. This article embarks on an in-depth exploration of this study, focusing on a case study of South Africa. Employing a qualitative content analysis methodology, the study draws from a comprehensive array of scholarly sources including articles, book chapters, and theses. In doing so, this articlenot only contributes to a deeper understanding of the complex interplay between cultural preservation and community empowerment but also underscores the enduring spirit and cultural richness of the African continent. This article provides valuable insights for scholars, practitioners, and policymakers engaged in the broader discourse on the African Renaissance and the pivotal role of indigenous music within it. This article concludes by mentioning that the quest for the restoration of the African Renaissance through indigenous South African music is a testament to the enduring spirit of the nation. It is evident that by embracing globalisation without compromising authenticity, South Africa exemplifies how a nation can reclaim its narrative and make meaningful contributions to the global cultural mosaic.